Morphological variability of the plantaris tendon in the human fetus - Anna Waśniewska-Włodarczyk; Friedrich Paulsen; Łukasz Olewnik; Michał Polguj (Scientific Reports, 2021)
Abstract Muscular anatomy often differs between species and individuals. In particular, the plantaris muscle (PM) demonstrates great morphological variability in its course and its proximal and distal attachments. The aim of this study was to investigate the morphological variation of the PM tendon in human fetuses. Forty-six spontaneously aborted human fetuses (23 male, 23 female) aged 18–38 weeks of gestation were studied. Morphology of the attachment of the PM was assessed in both lower extremities (n = 92). The PM was present in 72 lower limbs (78.26%) and absent in 20 (21.74%). Eight types of PM distal attachment were identified. We propose an eight-fold classification of PM insertion in fetuses. Leg length, length of tendon, extension point (ExP) from the calcaneus, and ExP thickness differed significantly among types of PM insertion.